Costal chondrosarcoma in a woman with hereditary multiple exostoses - a case report - Yang, Ze; Wang, Kaiqiang; Pu, Jiangtao (Frontiers in Oncology, 2025)
In this report, we present a case of a 32-year-old female previously diagnosed with hereditary multiple exostoses(HME) who was incidentally found to have an asymptomatic anterior mediastinal mass during a routine examination. Computed tomography imaging revealed a well-defined mass measuring approximately 2.3 cm x 4.0 cm x 4.7 cm in the anterior mediastinum with multiple nodular areas of high density within. The mass caused compression and narrowing of the right ventricle. The patient subsequently underwent intralesional resection of the tumor, and histopathological examination confirmed a diagnosis of well-differentiated chondrosarcoma. Given the patient’s medical history, the chondrosarcoma was suspected to have originated from malignant transformation of a rib osteochondroma. The patient received adjuvant radiotherapy postoperatively and has been followed up for one year with no evidence of recurrence. This case reports a highly rare costal chondrosarcoma secondary to hereditary multiple exostoses, located in the anterior mediastinum and compressing the right ventricle. To our knowledge, this is the first reported case of costal chondrosarcoma secondary to HME occurring in the anterior mediastinum, which requires differentiation from other common anterior mediastinal tumors.